The Legacies of Fazlur Rahman for Islam in American - Earle H. Waugh (International Institute of Islamic Thought, 1999)
In this paper, a student of Fazlur Rahman advances critical reflections on the meaning of Fazlur Rahman's work to the development of Islamic thought and under.,tanding among Muslims of America The paper not only examines Rahman's impact on Islamic thought but also explores his influence on the American academy. How the presence of an Islamic thinker affected the secular neutrality of American univer.,ities and the study of religion itself is an important aspect of this article. The author explores Rahman's endeavor., to remind the West of its Islamic heritage and his challenge to Muslims to reinterpret their traditions. The author seeks finally to identify the methodological basis of Fazlur Rahman's ????ork and how it enriched the tradition of Islamic modernism.